THE EFFECT OF PERSONAL SELLING AND MARKETING ON FIRM SALES GROWTH (A STUDY OF PZ AND DANGOTE NIGERIA PLC) - Adewale, Adegbite Ganiu; Adeniran, Ademola Joshua; Oluyinka, Solomon Ayodele (IJRDO - Journal of Business Management, 2019)
This paper critically examined the effect of personal selling and marketing on firm sales growth using PZ Nigeria Ltd, Lagos-State and Dangote Nigeria Plc, in Ogun state as the unit of analysis. This is a descriptive study. A sample size of 100 respondents selected with the aids of convenient sampling technique of which 98 respondents considered usable in this concluded study. Statistical package for social science (SPSS) version 20 adapted to the data from the questionnaire. This study justified there is a relationship between personal selling and organizational sales volume. Also, personal selling has an influence on customers demand for a product and therefore this study recommended that sales representative of an organization should be well trained on what is expected from them on the job. This would enable them to be able to convince the customers as to why they need to purchase such a specific product.